2018
DOI: 10.1111/jcmm.13734
|View full text |Cite
|
Sign up to set email alerts
|

Kallistatin attenuates endothelial senescence by modulating Let‐7g‐mediated miR‐34a‐SIRT1‐eNOS pathway

Abstract: Kallistatin, a plasma protein, protects against vascular and organ injury. This study is aimed to investigate the role and mechanism of kallistatin in endothelial senescence. Kallistatin inhibited H2O2‐induced senescence in human endothelial cells, as indicated by reduced senescence‐associated‐β‐galactosidase activity, p16INK 4a and plasminogen activator inhibitor‐1 expression, and elevated telomerase activity. Kallistatin blocked H2O2‐induced superoxide formation, NADPH oxidase levels and VCAM‐1, ICAM‐1, IL‐6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 59 publications
0
20
1
Order By: Relevance
“…Furthermore, there was a strong correlation between SIRT1 expression level in the kidney and a decrease in the total perfused peritubular cross-sectional area and PTC number ( Figure 5 C ), suggesting that SIRT1 activation facilitates PTC construction. Since eNOS has been reported to be a downstream target of SIRT1 37 , we hypothesized that the SIRT1/eNOS axis mediates the angiogenic response induced by GDNF-AMSC-exos. Western blotting revealed that treatment with GDNF-AMSC-exos significantly increased eNOS phosphorylation ( Figure 5 D ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there was a strong correlation between SIRT1 expression level in the kidney and a decrease in the total perfused peritubular cross-sectional area and PTC number ( Figure 5 C ), suggesting that SIRT1 activation facilitates PTC construction. Since eNOS has been reported to be a downstream target of SIRT1 37 , we hypothesized that the SIRT1/eNOS axis mediates the angiogenic response induced by GDNF-AMSC-exos. Western blotting revealed that treatment with GDNF-AMSC-exos significantly increased eNOS phosphorylation ( Figure 5 D ).…”
Section: Resultsmentioning
confidence: 99%
“…As a deacetylase, SIRT1 stimulates antioxidant enzymes including eNOS, catalase, and superoxide dismutase (SOD), and eNOS through NO production stimulates SIRT1 enzymatic activity and inhibits NADPH oxidase activity [58, 59], leading to the attenuation of oxidative stress. Similarly, kallistatin exerts salutary effects in the setting of H 2 O 2 -induced endothelial senescence, oxidative stress, and inflammation, as indicated by reduced p16 INK4a , PAI-1, and miR-34a synthesis, NADPH oxidase activity/expression, vascular cell adhesion molecule- (VCAM-) 1 and intercellular adhesion molecule- (ICAM-) 1 expression, and increased telomerase activity in endothelial cells [60]. Moreover, kallistatin via upregulating the endoprotective miRNA Let-7g coordinates Let-7g-modulated miR-34a-SIRT1-eNOS pathway and achieves antisenescent, antioxidant, and anti-inflammatory actions in endothelial cells [60].…”
Section: Kallistatin Reduces Senescence In Epcs and Endothelial Cellsmentioning
confidence: 99%
“…Similarly, kallistatin exerts salutary effects in the setting of H 2 O 2 -induced endothelial senescence, oxidative stress, and inflammation, as indicated by reduced p16 INK4a , PAI-1, and miR-34a synthesis, NADPH oxidase activity/expression, vascular cell adhesion molecule- (VCAM-) 1 and intercellular adhesion molecule- (ICAM-) 1 expression, and increased telomerase activity in endothelial cells [60]. Moreover, kallistatin via upregulating the endoprotective miRNA Let-7g coordinates Let-7g-modulated miR-34a-SIRT1-eNOS pathway and achieves antisenescent, antioxidant, and anti-inflammatory actions in endothelial cells [60]. Activation of SIRT1-eNOS signaling results in increased catalase and NO levels, thus suppressing oxidative vascular damage [60].…”
Section: Kallistatin Reduces Senescence In Epcs and Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heparin-binding site of kallistatin blocks high mobility group box 1 (HMGB1)-induced inflammatory gene expression in endothelial cells [17]. Kallistatin increases endoprotective miRNA Let-7g synthesis and through Let-7g induction stimulates eNOS, causing inhibition of oxidative stress and inflammation in endothelial cells ( Figure 1) [18]. Possibly kallistatin through active site interaction with tyrosine kinase stimulates Let-7g synthesis.…”
Section: Characteristics Of Kallistatinmentioning
confidence: 99%